Human Interface Research of Civil Aircraft Cockpit Based on Touch Control Technology. (August 2019) - Yang, Wen; Sun, Qin; Gao, Xiaolong; Dong, Dayong; Ma, Xianchao
Abstract: Touch screen technology is an important direction of the aircraft cockpit technology development. More and more touch screen test units are applied in the cockpit. However, most of the touch screen interface design is only a simple copy of the physical interface, which does not bring any benefits to the aircraft, but will cause some safety effects. Fundamentally speaking, these test units did not consider the impacts of flight crew operating procedures, human factors, flight scenes, and other factors on touch screen technology. This paper gives some advantages and disadvantages analysis for the touch control technology and provides a new concept of cockpit overhead control panel based on the touch control technology. The overhead touch control panel can not only effectively reduce the workload of the pilot, reduce the weight of the system, but also ensure the same flight safety with the physical panel. Keywords. Touch Control, Human Factor, Workload, Hybrid Layout, Ergonomics Evaluation.